The effects of Lactobacillus plantarum inoculation of spontaneously fermented cassava pulp (SFCP) on the quality, feed intake and growth of Lao-native beef steers - Napasirth, P.; Wachirapakorn, C.; Napasirth, V. (International Journal of Agricultural Technology, 2021)
The inoculated with Lactobacillus plantarum at concentration of 1.0 x 105 CFU/g FM showed the diet’s protein contents of 14.39% DM, while the uninoculated was 13.30% DM. The pH values of the uninoculated spontaneously fermented cassava pulp (SFCP) were higher than the inoculated cassava pulp (P<0.01), while the pH of the fermented total mixed ration (FTMR) was not affected by inoculant addition (P>0.05). Total feed intakes were not significantly different between the treatments except during 60 days of the experiment, which showed that the feed intake of uninoculated FTMR was higher than the inoculated FTMR (P<0.01). Overall, ruminal pH, NH3-N, and BUN were not affected by diet. However, steers were fed FTMR inoculated with L. plantarum, which significant affected on ADG and FCR compared to the control during 60 days after feeding period. The study indicated that SFCP inoculation with L. plantarum can improve the quality of the SFCP in the laboratory, whereas inoculated FTMR with L. plantarum was not decreased pH value. Finally, steers fed FTMR with inoculation had shown more significant ADG and FCR at 60 days after feeding